INFLUENCE OF ENDOPHYTIC BACTERIAL CONSORTIUM ON MAIZE RHIZOSPHERIC SOIL NUTRIENT STATUS UNDER MOISTURE STRESS CONDITIONS - M. UMA SOWJANYA, (The Journal of Research ANGRAU, 2024)
Under conditions of moisture and nutrient limitations growth of the plants is greatly reduced. The investigation was aimed to evaluate the developed endophytic bacterial consortium which is an alternative approach to minimize the use of chemical fertilizers and to mitigate stress conditions in maize under field conditions during Rabi of 2020-21. The available nitrogen in soil was more in T9 (225.29 kg ha-1) and T8 (209.09 kg ha-1), available phosphorous was higher in T9 (70.34 kg ha-1) and T8 (69.92 kg ha-1), available potassium is more in T9 (390.62 kg ha-1), T8 (360.59 kg ha-1). Soil enzyme activity has shown significantly higher in microbial inoculated treatments than control. Dehydrogenase activity was found higher in T9 (58.90 ìg of TPF g-1 of soil day-1) at flowering stage and maximum phosphatase activity was found in T8 (94.97 pNP g-1 of soil h-1). This research advocates the use of endophytic microbial consortium to mitigate stress and to improve soil nutrient status which ultimately enhances the plant health and yield.